Integrasi Penyimpanan Data dan Keamanan Jaringan Kantor KEMENAG Menggunakan Metode PPDIOO - Hadi, Abdul; Herkules, Herkules; Maryamah, Siti (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
Poor network design can lead to various issues, such as limited performance, increased operational costs, higher security risks, and difficulties in managing and monitoring network infrastructure. The KEMENAG XYZ office currently operates a local network with multiple wireless modem devices that are not interconnected, resulting in inefficiencies and security challenges in organizational data management.This study aims to implement centralized data storage and network device hardening to support the revitalization program for the use of information and communication technology as well as the optimization of public information transparency at the KEMENAG XYZ city office. The research adopts the Prepare, Plan, Design, Implement, Operate, and Optimize (PPDIOO) methodology by leveraging both hardware and software network technologies.The expected outcomes include a new network infrastructure topology design, more structured data management, and the implementation of enhanced security measures for network devices